2015
DOI: 10.1080/01425692.2014.987728
|View full text |Cite
|
Sign up to set email alerts
|

Can higher education compensate for society? Modelling the determinants of academic success at university

Abstract: This paper examines the role that social characteristics play in determining the academic success of students who begin university with roughly similar entry grades. The data used were drawn from the administrative records of over 38,000 UK-domiciled undergraduate students from one British university between 1998 and 2009. Results show that the characteristics of entrants have varied only slightly over this period and intake is still largely in favour of 'traditional' entrants: namely those from professional o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The findings of the meta analysis by Crisp et al (2014) also show similar results. Admission test scores are also positively related with academic success at university (Smith, 2016) but they are weak predictors of it (Komarraju & Nadler, 2013;Soria et al, 2013). The year of study is found to be a moderator of their relationship (Luqman, 2013).…”
Section: High School Results and Admission Test Scoresmentioning
confidence: 99%
See 4 more Smart Citations
“…The findings of the meta analysis by Crisp et al (2014) also show similar results. Admission test scores are also positively related with academic success at university (Smith, 2016) but they are weak predictors of it (Komarraju & Nadler, 2013;Soria et al, 2013). The year of study is found to be a moderator of their relationship (Luqman, 2013).…”
Section: High School Results and Admission Test Scoresmentioning
confidence: 99%
“…Students from less prestigious schools perform better in medical universities (Puddey & Mercer, 2014) and also in general universities (Li & Dockery, 2014) than those from more prestigious schools. Further, schooling from English Medium schools (Ali et al, 2013) and studying in a state university (Smith, 2016) are associated with success. Student-centred instruction also promotes academic success (Severiens et al, 2015).…”
Section: Factors Of Tertiary Academic Success At Organization Level Ementioning
confidence: 99%
See 3 more Smart Citations